Competence-Based Leadership in Indonesian Hospital Settings: A Qualitative Study of Operational Coordination and Digital Adaptation - Budi Santoso; Rian Andriani; Yen Efawati (Asosiasi Ahli Administrasi Indonesia, 2026)
Hospitals industry increasingly require leaders who can integrate managerial, interpersonal, digital, and strategic capabilities with the technical demands of healthcare delivery. This study explored how competence-based leadership is understood and enacted west java in Indonesian hospital settings, particularly in relation to operational coordination, professional boundaries, and digital adaptation. A qualitative descriptive design was used. Six hospital directors or managers and ten unit heads or supervisors in participated between Data were generated through semi-structured interviews and supported by document review and field observation. The material was analysed using thematic analysis and reported with reference to COREQ and SRQR principles. Four themes were identified: (1) competence as practical work readiness rather than technical knowledge alone; (2) leadership as direction, coordination, and real-time problem solving; (3) professional boundaries and hierarchy as simultaneous sources of order and barriers to open collaboration; and (4) digitalisation as an expansion of competence requirements and leadership responsibilities. The findings suggest that competence-based leadership is best understood as a situated organisational practice through which leaders mobilise employee capabilities, translate standards into daily routines, bridge professional boundaries, and support digital workflows. Participants associated these practices with more consistent service processes, stronger coordination, and greater organisational adaptability. The study contributes a context-sensitive framework linking healthcare-context competence, operational leadership, relational coordination, digital competence, and continuous competence development. Hospitals should prioritise competency mapping, unit-based leadership development, psychological safety, digital mentoring, and performance feedback.